Randomised controlled trial assessing the impact of a nurse delivered, flow monitored protocol for optimisation of circulatory status after cardiac surgery. Issue 7460 (8th July 2004) - McKendry, Moira; McGloin, Helen; Saberi, Debbie; Caudwell, Libby; Brady, Anthony R; Singer, Mervyn
Abstract: Objective To assess whether a nurse led, flow monitored protocol for optimising circulatory status in patients after cardiac surgery reduces complications and shortens stay in intensive care and hospital. Design Randomised controlled trial. Setting Intensive care unit and cardiothoracic unit of a university teaching hospital. Participants 174 patients who underwent cardiac surgery between April 2000 and January 2003. Interventions Patients were allocated to conventional haemodynamic management or to an algorithm guided by oesophageal Doppler flowmetry to maintain a stroke index above 35 ml/m 2 . Results 26 control patients had postoperative complications (two deaths) compared with 17 (four deaths) protocol patients (P = 0.08). Duration of hospital stay in the protocol group was significantly reduced from a median of nine (interquartile range 7-12) days to seven (7-10) days (P = 0.02). The mean duration of hospital stay was reduced from 13.9 to 11.4 days, a saving in hospital bed days of 18% (95% confidence interval −12% to 47%). Usage of intensive care beds was reduced by 23% (−8% to 59%). Conclusion A nurse delivered protocol for optimising circulatory status in the early postoperative period after cardiac surgery may significantly shorten hospital stay.